Reconsidering Climate Mitigation Policy in the UK - Arregui, Nicolas; Parry, Ian. (Washington, D.C. : International Monetary Fund, 2020)
The UK has pledged to cut greenhouse gases 57 percent below 1990 levels by 2030, to be emisisons neutral by 2050, and to phase out internal combustion engine vehicles by 2030. Much progress has been made, but fully achieving these ambitious objectives with the current policy framework will be challenging as it involves multiple and overlapping pricing schemes with significant sectoral differences in carbon prices and may be difficult to scale up on political and administrative grounds. This paper discusses an alternative framework consisting of: (i) a comprehensive carbon price (ideally a tax) rising to at least a60 (US USD 75) per ton by 2030; and (ii) reinforcing sectoral policies, most importantly feebates for the transport, industrial, and building sectors. This framework could implement mitigation targets, while limiting burdens on households and firms to enhance acceptability, and still raise revenues of 0.8 percent of GDP in 2030. The UK could also leverage its COP26 presidency to promote dialogue on international carbon price floors and pricing of international transport emissions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet